Pituitary Volumes Are Reduced in Patients with Somatization Disorder - Yildirim, Hanefi; Atmaca, Murad; Sirlier, Burcu; Kayali, Alperen (Korean Neuropsychiatric Assoc, 2012)
Objective Despite of the suggested physiological relationship between somatoform disorder and disturbances in HPA axis function no volumetric study of pituitary volumes in somatization disorder has been carried out. Therefore, we aimed to use structural MRI to evaluate the pituitary volumes of the patients with somatization disorder. Methods Eighteen female patients with somatization disorder according to DSM-IV and same number of healthy controls were included into the study. All subjects were scanned using a 1.5-T General Electric (GE; Milwaukee, USA) scanner. Pituitary volume measurements were determined by using manually tracings according to standard:antomical atlases. Results It was found significantly smaller pituitary volumes of the whole group of somatization patients compared to healthy (t=-3.604, p=0.001). ANCOVA predicting pituitary volumes demonstrated a significant main effect of diagnostic group (F=13.530, p<0.001) but TBV (F=1.924, p>0.05) or age (F=1.159, p>0.05). It was determined that there was no significant correlation between smaller pituitary volumes and the duration of illness (r=0.16, p>0.05) in the patient group. Conclusion In conclusion, we suggest that the patients with somatization disorder might have significantly smaller pituitary volumes compared to healthy control subjects. Psychiatry Investig 2012;9:278-282
Keywords: Somatization disorder; MRI; Pituitary; Volume